2004
DOI: 10.1021/cg049955+
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Additives on Nucleation of Vanillin:  Experiments and Introductory Molecular Simulations

Abstract: Nucleation of vanillin (VAN) in 2-propanol/water in the presence of additives, viz., acetovanillone (AVA), ethyl vanillin (EVA), guaiacol (GUA), guaethol (GUE), 4-hydroxyacetophenone (HAP), 4-hydroxybenzaldehyde (HBA), and vanillic acid (VAC) is investigated experimentally and by molecular simulations. In the experimental work, the induction time for nucleation is measured at different temperatures and levels of supersaturation using a multicell apparatus. A large variation in the experimental data is observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14] The second category encompasses the experiments where a macroscopic system property (such as transmittivity or turbidity), which is related to the volume fraction of the crystals, is measured. 2,[15][16][17][18][19][20][21][22][23][24] Crystals are detected, and hence the detection time is measured, when such volume fraction exceeds a specic threshold value. This latter technique suffers from two weaknesses: rst, the quantitative relationship between the solid volume fraction and, for instance, turbidity is difficult to calibrate; secondly, the threshold value is extremely difficult to estimate and might well be dependent on a series of factors, e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] The second category encompasses the experiments where a macroscopic system property (such as transmittivity or turbidity), which is related to the volume fraction of the crystals, is measured. 2,[15][16][17][18][19][20][21][22][23][24] Crystals are detected, and hence the detection time is measured, when such volume fraction exceeds a specic threshold value. This latter technique suffers from two weaknesses: rst, the quantitative relationship between the solid volume fraction and, for instance, turbidity is difficult to calibrate; secondly, the threshold value is extremely difficult to estimate and might well be dependent on a series of factors, e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…28,35 These biomolecules are present at high concentrations in a variety of biomass sources, such as fruits, vegetables and wood, and also in many residues from industrial or agricultural activities. 25,3638 Their extraction from natural sources is usually carried out with mildly polar solvents such as alcohols, 39,40 due to their low solubility in water (the solubility of vanillin in water is 12.78 g L −1 and that of gallic acid is 12.14 g L −1 at room temperature). 41 Although no previous studies on the hydrotropic solubilization of gallic acid have been reported, the solubility of vanillin in aqueous solutions is already recognized to increase in the presence of typical hydrotropes, such as nicotinamide, sodium salicylate, resorcinol and citric acid.…”
Section: Introductionmentioning
confidence: 99%
“…As the induction time can be experimentally determined by the isothermal method at a constant supersaturation level, the induction time data are frequently used as a measure of the nucleation event to calculate the interfacial energy of the crystallized substance in the literature [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%